40.4: High Efficiency Blue Phosphorescent Organic Light‐Emitting Diodes with >57 cd/A, >50 lm/W, and>25 % External Quantum Efficiency. Issue 1 (June 2015) - Lan, Yi‐Hsin; Huang, Jau‐Jiun; Chuang, Ya‐Ting; Leung, Man‐kit; Chiu, Tien‐Lung; Lin, Chi‐Feng; Lee, Jiun‐Haw
Abstract : Blue phosphorescent organic light‐emitting diodes (PhOLEDs) was successfully fabricated by using newly imidazole‐based host doped with bis [2‐(4', 6'‐difluoro)phenylpyridinato‐ N, C2']iridium(III) picolinate with 57.24 cd/A, 50.42 lm/W and 25.67 % in external quantum efficiency.